PENGARUH PENERAPAN SISTEM AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - Eji Saroji (Jurnal Akuntansi UMMI, 2021)
In conducting its business, the company in this case can not be separated from the financial statements . The financial statements have an important role in the process of measurement and assessment of corporate performance as well as useful in decision making . Many parties such as management , shareholders , creditors , governments and others with an interest in the financial statements . Financial statements must be prepared in such a way so as to meet the needs of all those who need them. Based on the findings and observations that occur in the field ( initial research ) , In carrying out its operations , the company has constraints in preparing its financial statements , in this case the company has not made the recording of financial statements and structured and frequent errors in recording , since less berkompetennya sources human resources in the field of accounting . The Company only records in a simple financial reports and accounting systems in the financial statements have not been used properly . The company therefore difficult to make a tax return , and the owner of the enterprise is difficult for decision-making in carrying out operational activities .The study aims to determine the effects of the application of the accounting system of the quality of financial statements. Variables used in this reseach is the accounting system and the quality of financial statements Responden in this study were employees CV. Mutia Tour and Akbar Wisata Tour. Of the 30 questionnaires obtained can be used in data processing. Using data analysis IBM SPSS version 23. The statistical method used is simple linear regression test and test hypoteses using partial test (t test) and the coefficient of determonation (R2). After analysis found the partial accounting system affect the quality of financial reporting. The coefficient of determination indicates the effect of the accounting system of the quality of the financial statements at 28,2% while the rest of 71,8% are affected by other factors not examined.